2017
DOI: 10.1007/s00508-017-1270-3
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure profile is associated with microalbuminuria and retinopathy in hypertensive nondiabetic patients

Abstract: Non-dipping hypertension was associated with increased risk of hypertensive retinopathy and microalbuminuria. Blood pressure profiles should also be considered in assessing the risk for hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…As demonstrated in the Syst-Eur study, higher incidence of stroke and myocardial infraction was revealed in non-dipper patients [35]. In patients with circadian BP profile disorders such complications like LVH, microalbuminuria, thickening of the intima media in the carotid artery and neurological incidents are significantly more common [36,37,38]. Finding of increased incidence of concentric hypertrophy (CH) may partially explain the higher incidence of cardiovascular events in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in the Syst-Eur study, higher incidence of stroke and myocardial infraction was revealed in non-dipper patients [35]. In patients with circadian BP profile disorders such complications like LVH, microalbuminuria, thickening of the intima media in the carotid artery and neurological incidents are significantly more common [36,37,38]. Finding of increased incidence of concentric hypertrophy (CH) may partially explain the higher incidence of cardiovascular events in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hipertensi merupakan suatu penyakit yang menyebar dalam tubuh manusia yang diakibatkan oleh peningkatan tekanan darah yang melebihi batas normal. Peningkatan terjadi dalam kurun waktu yang cukup lama sehingga menyebabkan komplikasi pada organ tubuh manusia yang tidak dapat terlihat dengan jelas misalnya komplikasi di jantung, ginjal, otak, dan retina [1]- [3]. Salah satu gangguan atau komplikasi dari tekanan darah tinggi terdapat pada bagian Retina.…”
Section: Latar Belakangunclassified
“…A loss of nocturnal BP decline (non-dipping) is an independent predictor of cardiovascular risk and mortality [ 8 , 9 ]. Moreover, it is associated with a higher risk of microalbuminuria, hypertensive retinopathy [ 10 ] and asymptomatic lacunar infarction of the brain [ 11 ].…”
Section: Introductionmentioning
confidence: 99%